First report of Capillaria plica Rudolphi, 1819 (Nematoda: Enoplida: Capillariidae) infection in a puma, Puma concolor Linnaeus, 1771 (Carnivora: Felidae) from southern Brazil - Marinho de Quadros, Rosiléia (2025)
Capillaria plica Rudolphi, 1819, a parasitic nematode, infects the urinary tract of both domestic and wild carnivores. Despite its global presence, clinical reports are rare in certain regions, including Brazil. This study documents the first occurrence of C. plica in a Puma concolor Linnaeus, 1771 (Puma) from Santa Catarina, southern Brazil, marking the first report of this parasite in the southern part of the country. Necropsy and urinary sediment analysis revealed the presence of C. plica eggs and adult nematodes. The parasite's diagnosis is challenging due to its subclinical nature and the difficulty in visualizing eggs and adults, especially in wild felids. This case highlights the importance of urinalysis in wild carnivores for diagnosing urinary capillariasis and emphasizes the need for heightened awareness of this parasitic disease, particularly in under-researched regions.